Penatalaksanaan Fisioterapi Pada Kasus Post Operasi Fraktur Cruris Sinistra Di RST. DR. Soedjono Magelang - Rivaldi, Dherian Mufty; , Agus Widodo SST.FT, M.Fis (2015)
Background: Scientific paper physiotherapy management in cases of post operative fracture in the left cruris RST dr, SoedjonoMagelang intended to provide information, knowledge, and understanding on condition of postoperative fracture cruris that cause physical problems such as pain, limitation of motion, edema, and decreased muscle strength and modality that is given in these conditions is infrared, free movemen active, passive movement, static contraction and hold relax Objective: Paper this scientifically to determine the benefits of infrared and exercise therapy on fracture cases cruris to help reduce pain, improve ankle motion, reduce swelling, increase muscle strength and improve functional ability. Methods: A case study of infrared, active movement, passive movement, static contraction and hold relex after 6 X therapeutic treatment obtained results Result: pain reduction motion in ankle measured by VAS scale at the start of physiotherapy (T1):5 to the end of the physiotherapy (T6):2 and tenderness in the ankle measured by VAS scale at the start of physiotherapy (T1):3 into the end fisioterai (T6):1 an increase in ankle motion (T1):S = 50-00-150 being the end of physiotherapy (T6):S = 180-00-300 decrease edema were initially (T1)= 56 to the end of physiotherapy menjad (T6):50 increasing muscle of such power that initially (T1)= 3- until the end of the physiotherapy into (T6):4- Conclusions and suggestions: it can be concluded that there is success in helping to reduce pain and tenderness of motion, increase ankle range of motion, increase muscle strength and improve funsional certainly in the right direction. The next suggestion is to maintain the health and be more careful to avoid accidents. Keywords: frakurcruris, infrared, free movemen active, passive movement, static contraction and hold relex